Corporate financial accounting - Carl S. Warren; Jefferson P. Jones (Boston, MA : Cengage Learning, 2019)
Gain a solid foundation in the core accounting concepts as you develop a true appreciation for why accounting is important to business and a prosperous society with Warren/Jones$1 (BCORPORATE FINANCIAL ACCOUNTING, 15E. Available with CNOWv2, this latest edition clearly demonstrates how accounting is more than just data or black-and-white rules. Instead, you see how accounting provides key information that professionals use to make critical business decisions.s
Keywords: Accounting; Managerial accounting; Corporations Accounting